The Relationship of Knowledge About COVID-19 and Compliance With Hand Washing With Soap in Primary School-Age Children - Rachmawaty D Hunawa; Dea Aprilya A. Mano; Suwarly Mobiliu; Nirwanto K. Rahim; Ita Sulistiani basir; Suwardha Yunus (PT.Mantaya Idea Batara, 2023)
Covid-19 is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). One part of the body that can transmit it is the hands. Washing hands with soap is one way to prevent the transmission of Covid-19. This study aims to determine the relationship between Covid-19 knowledge and hand washing using soap in elementary school-aged children at MIM Unggulan of Gorontalo City. This research is quantitative research with a cross sectional approach. The population are 167 elementary school students in grades 4 and 5. The total samples are 118 respondents using the Proportionate Stratified Random Sampling. The results showed that 88 respondents (74.6%) had good knowledge about Covid-19, 28 respondents (23.7%) had adequate knowledge, and two respondents (1.7%) had poor knowledge. In addition, respondents with good compliance with hand washing using soap were 85 respondents (72.0%), fair compliance were 32 respondents (27.1%), and one respondent with poor compliance (0.8%). It obtained p-Value = 0.000 (a < 0.005), which means that there is a relationship between Covid-19 knowledge and hand washing using soap compliance in elementary school-aged children at the MIM Unggulan of Gorontalo City.